THE EFFECT OF FINANCIAL PERFORMANCE, FIRM SIZE, AND ASSET GROWTH ON CAPITAL STRUCTURE - Desvi Nurdiana Nabila Fitrianingrum; Suhendro; Endang Masitoh (Kusuma Negara Business School, 2020)
This study aims to examine and analyze the effect of Financial Performance (Return On Assets and Current Ratio), Company Size, and Asset Growth on the Capital Structure of Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2016-2018. The independent variables in this study are return on assets, current ratio, company size, and asset growth. The dependent variable in this study is the capital structure. The sampling method uses purposive sampling. The sample in this study is 31 property and real estate companies in the 2016-2018 period, according to the criteria that have been determined to total of 93 companies over a three-year period. The analytical method used is multiple regression analysis using SPSS version 17.0. The results of this study Return On Asset, Current Ratio, Company Size, and Asset Growth simultaneously influence the Capital Structure. Partially Return On Assets and Asset Growth do not affect the Capital Structure, while the Current Ratio and Firm Size affect the Capital Structure. The benefit of this research is that it can broaden horizons and simultaneously gain knowledge about the effect of return on assets, current ratio, company size, and asset growth on capital structure.